The labor market in Italy, 2000-2016 - Francesca Marino; Luca Nunziata (IZA World of Labor, 2017)
The Italian labor market suffered a sizable negative shock from the double-dip recession and has since experienced a moderate recovery beginning in 2014. Despite some improvement, unemployment remains higher than pre-crisis levels, especially for young workers. Female participation has been slowly increasing. Regional heterogeneity is still high, with the stagnating south unable to catch up with the north. Real earnings have been increasing, but productivity is stable at relatively low levels compared to other European countries. Finally, undeclared employment is high, especially in the south.
Keywords: J01; J21; 330; Italy; unemployment; earnings; participation; young; south